WEBSITE PEMESANAN SABLON KAOS MENGGUNAKAN FRAMEWORK BOOTSTRAP DAN PHP - Andika Ilham Pradana (PT. Hasba Edukasi Mandiri, 2025)
This research discusses the design and creation of a web-based custom t-shirt screen printing ordering website that utilizes the Bootstrap framework for the front-end and PHP for the back-end. This system is designed to make it easier for customers to place orders remotely. This website implements HTML5, CSS3, and Bootstrap 5 to provide a much more attractive and responsive appearance, while data processing is done through PHP scripts. This website includes home, product, order pages, as well as form handling and dynamic displays. The result achieved is a basic prototype of a custom t-shirt screen printing ordering system that can be used by MSMEs.